Review of Criminal Law on The Practice of Cockfighting Gambling In Civil Activities In Mamasa (Case Study of Mamasa Regency) - Laitupa, Salma; Fadli Yasser (Kirana Publisher (KNPub), 2022)
In customary activities in the Mamasa community, we can find an activity called Rambusolo, where this activity is a customary activity in every death event in honor of those who have died. In this study the authors used a type of qualitative research by visiting the research location and conducting interviews with informants who were considered competent and knew about the cases raised. The data sources for this research are primary data sources obtained from interviews and direct observation and also secondary data sources obtained from books and other literature as well as existing journals. Rambusolo is a traditional Mamasa regency activity which is still maintained today. In this activity, several traditional rituals are carried out, such as buffalo fights, cockfights, etc. In cockfighting activities there are several activities that use money fights in the form of gambling, while our positive law clearly prohibits it strictly in the Criminal Code, articles 303 and 303 bis.